Professional Training of Future Specialists in the Field of Technology and Design Using Digital Technologies - Yezhova, Olga (Journal of Vasyl Stefanyk Precarpathian National University, 2024)
The article substantiates the relevance of the problem of using digital technologies in the professional training of future specialists in the field of technology and design. A theoretical analysis of scientific sources for understanding the concepts of “professional training”, “digitalization”, “digital technologies” was carried out. It was found that the technological education of young people plays an important role in the formation of critical and technical thinking, the ability to change the environment by means of modern technologies and design, gaining experience in the step-by-step creation of useful and aesthetic products; development of skills to use traditional and modern technologies; the ability to entrepreneurship and innovative actions, the formation of a work culture, the desire to improve the process and results of design and technological activity, as well as the determination of the sphere of future professional activity, which depends on the well-being and economic power of the state. It was concluded that digital technologies are an effective means of professional training of future specialists in the field of technology and design, which ensure the achievement of an atmosphere of cooperation, understanding and benevolence, contribute to the formation of critical and technical thinking skills and abilities, the development of creative potential and self-realization, the achievement of new educational results, adequate to the requirements of the digital society. At the same time, digital technologies make it possible to make the process of professional training of future specialists in the field of technology and design mobile, differentiated and individual based on the implementation of innovative approaches, including the use of Google services, E-manuals, multimedia presentations, the use of web quests, “cases” , project method, etc. The digital transformation of Ukrainian education strengthens the motivation of future specialists for self-education and self-development, contributes to the achievement of new educational results adequate to the requirements of a digital society. Digital technologies are effective means that enable individuals to be prepared for active life in society and allow for the editing, expansion and improvement of social experience.